In vitro anti-inflammatory, cytotoxic and antioxidant activities of boesenbergin A, a chalcone isolated from Boesenbergia rotunda (L.)(fingerroot) - Isa, N. M.; Abdelwahab, S. I.; Mohan, S.; Abdul, A. B.; Sukari, M. A.; Taha, M. M. E.; Syam, S.; Narrima, P.; Cheah, S. C.; Ahmad, S.; Mustafa, Mohd Rais (Associacao Brasileira de Divulgacao Cientifica, 2012)
The current in vitro study was designed to investigate the anti-inflammatory, cytotoxic and antioxidant activities of boesenbergin A (BA), a chalcone derivative of known structure isolated from Boesenbergia rotunda. Human hepatocellular carcinoma (HepG2), colon adenocarcinoma (HT-29), non-small cell lung cancer (A549), prostate adenocarcinoma (PC3), and normal hepatic cells (WRL-68) were used to evaluate the cytotoxicity of BA using the MTT assay. The antioxidant activity of BA was assessed by the ORAC assay and compared to quercetin as a standard reference antioxidant. ORAC results are reported as the equivalent concentration of Trolox that produces the same level of antioxidant activity as the sample tested at 20 µg/mL. The toxic effect of BA on different cell types, reported as IC50, yielded 20.22 ± 3.15, 10.69 ± 2.64, 20.31 ± 1.34, 94.10 ± 1.19, and 9.324 ± 0.24 µg/mL for A549, PC3, HepG2, HT-29, and WRL-68, respectively. BA displayed considerable antioxidant activity, when the results of ORAC assay were reported as Trolox equivalents. BA (20 µg/mL) and quercetin (5 µg/mL) were equivalent to a Trolox concentration of 11.91 ± 0.23 and 160.32 ± 2.75 µM, respectively. Moreover, the anti-inflammatory activity of BA was significant at 12.5 to 50 µM and without any significant cytotoxicity for the murine macrophage cell line RAW 264.7 at 50 µM. The significant biological activities observed in this study indicated that BA may be one of the agents responsible for the reported biological activities of B. rotunda crude extract.